Effect of nanoclay addition on the mechanical properties of glass fibre reinforced epoxy nanocomposites processed through VARIM - Shelly, Daksh (My University, 2016)
Now days, glass fibre reinforced nanocomposites are replacing metals in many weight-critical components in military, aviation, automotive, and other industries due to properties shown by them are comparable or better than the traditional metallic materials because of their low density, high strength-weight ratios, and high modulus-weight ratios. The objective of this research work is to “Effect of nanoclay addition on the mechanical properties of glass fibre reinforced epoxy nanocomposites processed through VARIM.” The epoxy resin and hardener used were CY 230-1 and HY 951 respectively. E glass fibre was used as reinforcement and nanoclays were used as nanofiller. Nanoclays used were Nanomer PGV and Nanomer I.28E. Nanoclay was mixed in epoxy resin by using mechanical stirrer followed by homogenization and probe sonication. Vacuum assisted resin infusion moulding (VARIM) was used to fabricate the glass fibre reinforced epoxy nanocomposites. The nanoclay content was varied form 0–4 phr. Tensile, flexural, fracture toughness and impact strength testing were evaluated according to ASTM D-3039, ASTM D 790–02, ASTM D 5045–99 and ASTM D 256–02 ε1 respectively. XRD and TEM analysis were used to study the morphology of the fabricated nanocomposites. SEM analysis was used to characterize fracture mechanisms involved during mechanical testing. XRD micrographs revealed that full or partial exfoliated morphology was observed for NV1 and NE1 formulations whereas, intercalated morphology was observed for NV2, NV4, NE2, and NE4 formulations. TEM results were also confirming the XRD results. The best tensile and flexural properties were observed in nanocomposite containing 1 phr Nanomer PGV (NV1 formulation). Whereas, best impact strength and fracture toughness were observed in nanocomposite containing 2 phr of Nanomer PGV (NV2 formulation). The nanocomposites fabricated using Nanomer PGV showed better properties as compared to Nanomer I.28E. SEM micrographs of fractured surface of glass fibre reinforced epoxy composite (reference sample) showed relatively smooth surface and indicated that the interfacial bonding between the glass fibre and the epoxy was weak. However, the fractured surfaces of nanocomposites containing 1 and 2 phr nanoclay looked rougher and were indicating a strong interface bonding between glass fibre and epoxy clay matrix. The SEM micrographs of nanocomposites with 4 phr nanoclay suggested that silicate platelets were not able disperse properly and resulted in formation of clay agglomerates or tactoids. These agglomerates of silicate platelets may act as crack initiating sites which may be the possible reason for deteriorated properties.
ME, MED
Keywords: Epoxy; nanoclay; nanocomposites; glass fibres